PERANCANGAN DAN PEMBANGUNAN SISTEM OTOMASI BERBASIS IOT PADA PERTANIAN HIDROPONIK - Afif, Ramadhan Nur; Rozikin, Chaerur; Sari, Betha Nurina (Jurnal Ilmiah Wahana Pendidikan, 2024)
Hydroponics is a growing method that replaces soil with water. It means you can grow anywhere without worrying about soil quality. And that makes water important for hydroponics. The amount of nutrients and the pH of the water affect the plants. The ideal pH for hydroponic plants is around 5.5 - 6.5 on average. The amount of nutrients in the water varies depending on the type of plant. This research uses TDS, pH and float switch sensors connected to the ESP32, which then communicates with the Blynk application. This application can be monitored and managed via the internet. This application is available on android, ios and Web. The test is performed on the tank by setting the target value. The results of calibrating the pH sensor using the one-point method are stable, giving relatively good measurement results.